Facts about Vitamin D - Linda B. Bobroff; Isabel Valentin-Oquendo (EDIS, 2006)
Revised! FCS-8640, a 2-page fact sheet by Linda B. Bobroff and Isabel Valentin-Oquendo, has been updated with new graphics and includes reference to fortified orange juice as a food containing vitamin D. Published by the UF Department of Family Youth and Community Sciences, April 2006.